Application of the calculation method for calculating an economically justified land tax - A. V. Ilin (Вестник университета)
The article considers the mechanism used to calculate the land tax. caused by the overestimation by the state of the cadastral value of land plots used as a tax base, which leads to the problem of economically unreasonable taxation for taxpayers. The directions for improving the mechanism of land tax calculation and changing the practice of taxation have been formed. The analysis of normative legal base, taxation practice, statistical data, economic publications devoted to the mechanism of land tax assessment has been carried out. The article contains judgments of the continuous presence of a significant overestimation of the tax base for the land tax in the tax system of Russia, which leads to the unreliable definition of the taxpayer’s tax liability. It is concluded that in case of disagreement of an organization or an individual with the amount of tax base, its revision is carried out within the framework of tax relations using the principle of economic feasibility and equality of taxation and calculation method developed by economic science to protect taxpayer’s rights.